Doing Family on the Move Highly-Skilled Migrants in Switzerland and Germany - Tissot, Florian (Peter Lang International Academic Publishers, 2020)
This book focuses on the coordination between family life and professional career under the condition of repeated mobilities. It analyses the division between the labour force work and the care work of couples of highly-skilled migrants settling in either Switzerland or Germany. A mutually exclusive model provides an innovative understanding of gendered hierarchies in career achievement. The male partners operate three parallel elements: an upward professional career, a family-life implying child(ren), and maintaining their availability to further unplanned relocations. The female partners can only coordinate two of these concurrently. In fact, the male partners combine the three elements by taking advantage of specific, and mostly invisible, care work that the female partner provides.